Muscle Oxygenation During Exercise in Physically Active and Overweight 6–19-Year-Old Children (Baltic Journal of Sport and Health Sciences, 2017)
Background. The purpose of our study was to compare muscle oxygenation during walking exercise in physically active, non-physically active normal weight and overweight 6–19- year-old children. Methods. Twenty four normal weight, physically non-active (NPA), 27 normal weight physically active (PA) and 17 overweight (OW) 6–19-year-old children participated in this study. Muscle oxygenation was recorded by near infrared spectroscopy during constant (6 min, 6 km/h, 4% grade) and increasing walking exercise (modifed Balke test). Heart rate was recorded using Polar system. Results. Overweight children of all age groups demonstrated slower time constant of muscle oxygenation during constant walking exercise (37.2 ± 3 (6–10-year-old); 29.7 ± 2 (11–15-yr old), 33.4 ± 5.1 (16–19-year-old)) and lower threshold of oxygenation (TO) (84.3 ± 10.1, 104.5 ± 17.1, 188.5 ± 69.4 respectively) during increasing walking exercise as compared NPA (111.8 ± 13.7, 124.4 ± 29.8, 192.6 ± 84 respectively) and PA (106.2 ± 35.2; 122 ± 13.3; 340.8 ± 44.2 respectively) peers. The time constant of Deoxy-Hb during constant walking exercise was the shortest in PA (16.7 ± 2.3, 16.9 ± 2, 15.5 ± 4.7 respectively) in all age groups. The TO was higher in PA as compared to NW only in 16–19 years of age. Conclusion. Muscle oxygenation during constant or increasing exercise is dependent on both body weight and physical activity status in 6–19-year-old children.Keywords: muscle oxygenation, children, physical activity, overweight.